The Result of Timely Therapy for Whipple's Disease: a Clinical Case - S. N. Mekhtiev; O. A. Mekhtieva; E. Yu. Kalinina; V. E. Karev; A. V. Vanyan; O. M. Berko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Аim: to provide basic information on Whipple's disease necessary for timely diagnosis and treatment, using the example of clinical observation.Key points. Whipple's disease is a rare systemic infectious disease that internists, gastroenterologists, rheumatologists, and other physicians may encounter. The incidence of Whipple's disease is extremely low and amounts to 1 case per 1,000,000–10,000,000 people. The low prevalence of pathology can lead to underdiagnosis in favour of more common diseases. This, in turn, may worsen the patient's prognosis, as it will delay the time for establishing the correct diagnosis and initiating the necessary therapy. A 50-year-old man complained of losing 10 kg of weight over 5 months, abdominal pain and bloating, pain in the joints of feet, and shoulders, accompanied by swelling and hyperemia. The disease began with articular syndrome followed by diarrhea and manifestations of malabsorption (iron deficiency anemia, hypoalbuminemia, hypercholesterolemia). The diagnosis was established on the basis of morphological changes in biopsy samples of the postbulbar part of the duodenum. The identified changes were represented by thickening of the villi and accumulations in the stroma of large macrophages (CD68+) with wide light cytoplasm containing abundant accumulations of PAS-positive, negative when stained with carbol fuchsin according to Ziehl — Nielsen and auramine-rhodamine (under microscopy in luminescence mode) short rods, as well as numerous optically empty small and larger cavities. Treatment with intravenous injections of ceftriaxone 2 g per day for 14 days and trimethoprim/sulfamethoxazole 1920 mg per day for 8 months led to improved health, normalization of laboratory parameters, endoscopic and morphological findings. Treatment with trimethoprim/sulfamethoxazole is planned to be continued for up to 12 months or longer if necessary.Conclusion. Timely diagnosis and initiation of antibiotic therapy will help to avoid late complications of the disease, including death.